Electrotropism of Maize (Zea mays L.) Roots (Facts and Artifacts). - Stenz, H. G. (1993)
Intact and decapped primary roots of maize (Zea mays L.) were exposed to DC electric fields of 0.5 to 8.0 V/cm in low-salinity media to resolve conflicting results about the direction of electrotropism. In DC fields of 0.5 V/cm or 1.0 V/cm, intact roots always curved toward the cathode. In a field of 8.0 V/cm, intact roots curved toward the anode and stopped growth. Decapped roots also curved toward the anode both in weak and strong fields. The results indicate that growth toward the cathode is the true response of healthy roots.